The Skyfire puzzle - Dixon, Franklin W. (New York : Wanderer Books, 1985)
When an important space mission is sabotaged at Cape Canaveral, the Hardy boys are called in to investigate.
On t.p. the registered trademark symbol "R" is superscript following "Boys" in the series area.
Keywords: Space flight -- Fiction; Mystery and detective stories; John F. Kennedy Space Center -- Fiction